Sehat Jiwa, Hidup Sejahtera: Psikoedukasi Pengelolaan Stres melalui Afirmasi Positif untuk Masyarakat di Desa Sijantung, Kepulauan Riau - Sondakh, Jessyca Tiara; Aisyah S , Annisa Siti; Salsalbillah, Viona Taj; Prameswari, Yuditia; Rochma, Izura (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Stress management is the skill to channel stress to avoid feeling depressed in order to balance your emotions. It was found that early adults in Sijantung Village lacked skills in stress management. Therefore, this community service aims to provide education on stress management. This service is carried out using a community-based educational method with various stages, namely: pre-survey, survey, implementation, and evaluation and closing. The location of the implementation of community service was carried out in Sijantung Village, Rempang, Galang. The result of this community service activity is that it has a significant positive impact. Participants showed a better understanding of the importance of mental health, which was previously often overlooked. They also learned to recognize and manage stress effectively through techniques such as writing positive affirmation sentences..